2017
DOI: 10.1056/nejmoa1615664
|View full text |Cite
|
Sign up to set email alerts
|

Evolocumab and Clinical Outcomes in Patients with Cardiovascular Disease

Abstract: BACKGROUND Evolocumab is a monoclonal antibody that inhibits proprotein convertase subtilisin–kexin type 9 (PCSK9) and lowers low-density lipoprotein (LDL) cholesterol levels by approxi - mately 60%. Whether it prevents cardiovascular events is uncertain. METHODS We conducted a randomized, double-blind, placebo-controlled trial involving 27,564 pa - tients with atherosclerotic cardiovascular disease and LDL cholesterol levels of 70 mg per deciliter (1.8 mmol per liter) or higher who were receiving statin thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

108
3,510
12
222

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 4,746 publications
(3,852 citation statements)
references
References 33 publications
108
3,510
12
222
Order By: Relevance
“…Consistent with the overall patient populations mentioned above,63, 78 subanalyses by diabetes mellitus status demonstrated that overall alirocumab/evolocumab safety was comparable to that of control in those with and without diabetes mellitus 66, 67, 69, 71, 80. Overall safety was also comparable versus control between patients with diabetes mellitus and ASCVD,68 insulin‐treated patients with diabetes mellitus in the DM‐INSULIN study,75 patients with T2D and mixed dyslipidemia in the DM‐DYSLIPIDEMIA study,77 individuals with prediabetes and normoglycemia,72 and those with and without dysglycemia or metabolic syndrome 73.…”
Section: Safety Of Pcsk9 Inhibitors In Patients With Diabetes Mellitusupporting
confidence: 71%
See 4 more Smart Citations
“…Consistent with the overall patient populations mentioned above,63, 78 subanalyses by diabetes mellitus status demonstrated that overall alirocumab/evolocumab safety was comparable to that of control in those with and without diabetes mellitus 66, 67, 69, 71, 80. Overall safety was also comparable versus control between patients with diabetes mellitus and ASCVD,68 insulin‐treated patients with diabetes mellitus in the DM‐INSULIN study,75 patients with T2D and mixed dyslipidemia in the DM‐DYSLIPIDEMIA study,77 individuals with prediabetes and normoglycemia,72 and those with and without dysglycemia or metabolic syndrome 73.…”
Section: Safety Of Pcsk9 Inhibitors In Patients With Diabetes Mellitusupporting
confidence: 71%
“…The inclusion/exclusion criteria and other details of each phase 3 ODYSSEY and PROFICIO trial are shown in Table S2. LDL‐C reductions in the placebo‐controlled phase 3 trials were consistent with those found in the FOURIER (Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects with Elevated Risk) cardiovascular outcomes trial (Table), studying evolocumab versus placebo in 27 564 patients with clinically evident ASCVD and on a moderate‐to‐high‐intensity statin regimen over a median follow‐up duration of 2.2 years 63. The GLAGOV (Global Assessment of Plaque Regression With a PCSK9 Antibody as Measured by Intravascular Ultrasound) study (which included 968 statin‐treated patients with angiographic coronary disease to evaluate the effect of evolocumab versus placebo on the progression of coronary atherosclerosis) also showed comparable reductions in LDL‐C levels over 76 weeks of evolocumab treatment (from 93 mg/dL at baseline to 37 mg/dL at week 76) 64.…”
Section: Pcsk9 Inhibitors and Their Effects In Patients With Diabetessupporting
confidence: 63%
See 3 more Smart Citations